Relevansi Metode Ilmiah Thomas Kuhn dan Keilmiahan Islam - Fatih Atsaris Sujud (Jurnal Filsafat Indonesia, 2022)
Science is a method of thinking objectively. The goal is to describe and give meaning to the factual world. The application of science is divided into 3, as a means of explanation, predictor and control. The scientific method consists of a series of activities in the form of: identification and formulation of problems, gathering relevant information, formulating hypotheses, conducting experiments and publication or dissemination of information. The scientific revolution is a process of transitioning from an old paradigm to a new one. With this paradigm shift, the perspective of scientists in determining problems, establishing methods and techniques, and drawing conclusions from natural realities will be different from the previous paradigm. The method used in this paper is a descriptive method in which to find the definitions contained in the problem to combine it into a narrative in order to explain the core problem. Thomas Kuhn's thoughts about the process of the birth of science can be contextualized in the thinking and dynamics of Islamic scholarship, especially in opening the mindset of Muslim scientists, that in fact in the dynamics of science, there is no absolute scientific truth, but there are always opportunities for the birth of new knowledge with scientific epistemology. which are sometimes more acceptable to society. Thus, in the context of Islamic scholarship, it shows that Islam has a basic grip on the Qur'an and al-Hadith which the Muslim community believes as truth and guidelines in life. Kuhn invited researchers to turn to a paradigmative viewpoint where this perspective expands the scope of science to every aspect of life, including in the social field.